2015
DOI: 10.1586/17474124.2015.1083419
|View full text |Cite
|
Sign up to set email alerts
|

Management of ascites in children

Abstract: Ascites is the pathologic accumulation of fluid within the peritoneal cavity. There are many causes of fetal, neonatal and pediatric ascites; however, chronic liver disease and subsequent cirrhosis remain the most common. The medical and surgical management of ascites in children is dependent on targeting the underlying etiology. Broad categories of management strategies include: sodium restriction, diuresis, paracentesis, intravenous albumin, prevention and treatment of infection, surgical and endovascular sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 55 publications
1
26
0
3
Order By: Relevance
“…Abdominal ultrasound is also helpful to evaluate liver and biliary anatomy and the portal system, as well as estimating the volume of the ascitic fluid. However, when the underlying etiology is unclear a diagnostic paracentesis could be necessary [5]. The patient herein reported was initially referred for IBD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdominal ultrasound is also helpful to evaluate liver and biliary anatomy and the portal system, as well as estimating the volume of the ascitic fluid. However, when the underlying etiology is unclear a diagnostic paracentesis could be necessary [5]. The patient herein reported was initially referred for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Budd-Chiari syndrome), infections (e.g. CMV, EBV, tuberculosis), inflammatory bowel disease (IBD), malignancies, omental cyst [5]. Noncirrhotic ascites can develop as a consequence of secretion of proteinaceous material (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,31 Albumin infusion is also recommended for pediatric patients with a blood albumin level ≤ 2.5 g/dL to promote extravascular water reabsorption, associated with loop diuretics to produce more diuresis. 2,87 It has been observed that albumin infusion and water restriction correct HH in children, and other authors have proposed this treatment for adults, 88 but there are no good-quality studies to support this recommendation. 8,89 Albumin infusion alone or together with vasopressors may also be useful for the management of HH.…”
Section: Therapeutic Options Albumin Prescriptionmentioning
confidence: 99%
“…5,8,31 La infusión de albúmina también se recomienda en pacientes pediátricos con albuminemias ≤ 2,5 g/dL para promover la reabsorción extravascular de agua, asociada a diuréticos de asa para producir mayor diuresis. 2,87 Hemos observado que la infusión de albúmina y la restricción hídrica corrigen la HH en niños, y otros autores proponen este tratamiento en adultos, 88 pero no existen estudios de buena calidad que avalen su recomendación. 8,89 La infusión sola o asociada a drogas vasoconstrictoras también podría ser útil para tratar la HH.…”
Section: Opciones Terapéuticas Prescripción De Albúminaunclassified